Defensive coping facilitated a smaller cortisol-to-estradiol ratio and a higher hypertension risk: the SABPA study. (3rd September 2018) - Malan, Leoné; de Kock, Andrea; Hamer, Mark; Cockeran, Marike; Malan, Nicolaas Theodor
Abstract: Objectives: Taxing psychosocial stress and defensive coping have been associated with hypoactivity in cortisol, a vasoconstrictive agent. Estradiol has vasodilatory properties with cardio- and neuroprotective effects. It can however also induce α1 -adrenergic vasoconstrictive responsiveness. We aimed to determine whether the cortisol-to-estradiol ratio (Cort:E2) may augment α1 -adrenergic responsiveness and hypertension risk when habitually using defensive coping. Methods: African ( n = 168) and Caucasian ( n = 207) men and women (46 ± 9 years) were included. Preferential use of defensive coping was determined from Coping Strategy Indicator questionnaire scores. 24h Ambulatory blood pressure was obtained. Fasting serum estradiol and cortisol samples were collected before 09h00 and Cort:E2 was calculated. Results: Estradiol was higher in ethnic-coping groups. Smaller Cort:E2, higher estradiol levels, self-reported emotional stress (19.05% vs. 9.66%) and 24h blood pressure reaching hypertensive status (65% vs. 24%) were evident in African compared to Caucasian men ( p ≤ .05). A smaller Cort:E2 was associated with augmented 24h SBP and 24h DBP in African men [Adj R 2 0.21–0.29 ( p ≤ .05)], and especially when utilizing defensive coping [Adj R 2 0.34–0.38 ( p ≤ .001)]. Conclusions: A smaller Cort:E2 was associated with raised blood pressure in defensive coping African men. Defensive coping, possibly via highly activated α1 -adrenergic vasoconstrictive responses, may facilitate neuro-endocrine dysfunction and hypertension in African men.